The orchestration of intangible resources in post-merger and acquisition: A case study of Trans7 in Indonesia - Badri Munir Sukoco; Juliani Dyah Trisnawati; Ishadi Sk; Maurice Lyver (Cogent Business & Management, 2022)
The post-M&A (merger and acquisition) transition period plays a critical role in the process that determines the success of M&A. Yet many questions remain about how to ensure M&A success after the signing ceremony. We show how resource orchestration is the main driver in delivering expected outcomes. Based on a single case study, we explore various mechanisms to orchestrate resources post-M&A in a broadcasting company in Indonesia. The findings indicate that the resource-orchestration process is similar to a bee colony. The owner is the dominant "queen bee" with a strong, charismatic leadership that determines M&A success. In this model, the owner's direction is enabled by the bee nurses (a board of commissioners or board of directors) to structure, bundle, and leverage a complex bundle of company's resources as well as search/select and configure/deploy the company's resources. Bee seekers (company division heads) search for business opportunity and meet customer needs through one-stop services. So-called bee collectors (programming and production division staff) follow up and execute on opportunities provided by bee seekers through innovative programming that satisfies customer needs and expectations. By using a bee colony model for orchestrating resources, we show how post-merger transitions can be smoothed and shortened, leading to greater expected outcomes.
Keywords: 650; innovation; bee colony model; broadcasting industry; merger and acquisition; resources orchestration